Evolving trends in nurse regulation: what are the policy impacts for nursing's social mandate?. Issue 1 (7th November 2014) - Duncan, Susan; Thorne, Sally; Rodney, Patricia
<x xml:space="preserve">Abstract</x> We recognize a paradox of power and promise in the context of legislative and organizational changes in nurse regulation which poses constraints on nursing's capacity to bring voice and influence to pressing matters of healthcare and public policy. The profession is at an important crossroads wherein leaders must be well informed in political, economic and legislative trends to harness the profession's power while also navigating forces that may put at risk its central mission to serve society. We present a critical policy analysis of the impact of recent regulatory trends on what the International Council of Nurses considers nursing's three 'pillars' – the profession of nursing, socioeconomic welfare of nurses and nurse regulation. Themes surfacing from this analysis include regulatory discontinuity, a tightening of regulatory control, and an increasingly managerial governance culture. These themes illuminate insights and strategies required to renew and revitalize the social mandate of our profession amidst a climate of urgency in the questioning of nurse scholars with respect to the future of the profession. At this historic juncture, nurses must clearly understand the implications of legislative and organizational regulatory changes to ensure the profession contributes to full capacity in achieving health and health equity globally.